Pengendalian Kualitas Blaine (Kehalusan) Semen Terhadap Kuat Tekan pada Industri Semen di PT.Semen Baturaja (Persero) Panjang - Zoraya User; Muhammad Amin (Balitbangda Provinsi Lampung, 2015)
Portland cement is produced by grinding cement klingker consisting of calcium silicate hydraulic. Important character of the cement is the compressive strength. The characters are quite affecting the compressive strength is blaine ( fineness of grain ) on cement ,because the fine grain cement it will also increase the compressive strength of cement. To determine the compressive strength of the cement, portland cement that has known its blaine value mixed with quartz sand with a certain ratio and the addition of water to form a dough and then molded into the shape of a cube with a size of 5 x 5 x 5 cm, after the age of 3, 7, and 28 days and undergoing treatment with subsequent immersion test specimens for compressive strength test. From the results, the effect of fineness of cement is proportional to the compressive strength. Based on testing conducted as many as 15 pieces of sample then obtained the smallest value of blaine (fineness of grain) is 3329 cm2/g with the compressive strength of 177 kg/cm2 at the third day, the compressive strength of 220 kg / cm2 at the seventh day and the compressive strength of 296 kg / cm2 at 28th day. While the biggest blaine (fineness of grain) value is 3658 cm2/g with the compressive strength of 231 kg/cm2 at the age of third day, the compressive strength of 282 kg/cm2 at the seventh day and the compressive strength of 363 kg / cm2 at the age 28th day. With the blaine value results as mentioned above, the grain fineness of cement that produced by PT.Semen BATURAJA ( Persero ) is compliant with the minimum standard that is equal to 2800 cm2 / g according to SNI 15-70642004standards blaine test results closely enough because figure shows the accuracy of the final figure of 3.616 %, which means that they meet the requirements of a margin of error of less than 5 %